Home environment and fall at home among the elderly in Masjid Tanah Province - Mahpot, Rizawati; Said, Mas Ayu (Faculty of Medicine, University of Malaya, 2008)
The aim of this study was to determine whether the home environment was a risk factor for falls occurring at home among the elderly in the Masjid Tanah community, Malaysia. An analytical cross-sectional study conducted from early June 2006 until May 2007 in six randomly selected villages in Masjid Tanah Province. A total of 516 participants were included in this study. Overall prevalence of falls among the study participants was 27.3%. Home falls accounted for 66.7% of the total falls. In conclusion, there was no association between home environment and home fall in this study. Logistic regression analysis showed that having a depressive mood was the main determinant for home falls among the elderly in this study.